Analisis Kadar Senyawa Flavonoid pada Daun Bawang Hutan (Eleutherine palmifolia (L.) Merr.) - Mitha Widya Ningrum; Siti Nuryanti (Universitas Tadulako, 2022)
Forest onion (Eleutherine palmifolia (L.) Merr.) is one of the plants commonly used by the community as traditional medicine. This plant can cure diseases such as diabetes mellitus, hypertension, prevent stroke and can lower cholesterol. Forest onions are known to contain compounds such as flavonoids, phenolics, tannins, and saponins. This study aims to determine the levels of flavonoid compounds in forest leek extract. Samples were extracted using maceration method with 70% ethanol as solvent. Determination of flavonoid levels using a UV-VIS spectrophotometer at a wavelength of 432.5 nm and using quercetin as a comparison (QE). The results of this study showed the levels of flavonoid compounds in forest leeks were 27.203 mg/100g±0,348.